The Impact of Sticking Pictures to Promote Dengue Fever Prevention on Fifth-Graders’ Knowledge and Attitude - Wibowo, Della Pangestu; Chifdillah, Nino Adib; Ardyanti, Dian; Hendriani, Dwi (Poltekkes Kemenkes Surakarta, 2024)
Background: Dengue fever is an acute mosquito-borne infection caused by the dengue viruses and has become a growing public health concern globally. One of the causes is the lack of knowledge about the 3M Plus campaign, especially among children in the school-age group. The objective of this research is to identify the impact of sticking pictures as health promotion media to prevent dengue fever on elementary school fifth-graders’ knowledge and attitude. Methods: This research uses a pre-experimental type with a one-group pre-test and post-test design. The population of this research consisted of all fifth-grade students, followed by 39 persons chosen utilizing proportional random sampling and simple random sampling techniques. The primary data for this research were collected through the distribution and completion of close-ended questionnaires. The data analysis method was carried out using the Wilcoxon signed-ranks test. Results: The results show that there is a significant impact of the use of sticking pictures as health promotion media on elementary school fifth-graders’ knowledge (p = 0.01) and attitude (p = 0.01) towards dengue fever prevention after they were given sticking pictures. Conclusion: The use of health promotion media with sticking pictures affects elementary school fifth-graders’ increasing knowledge and attitude about DHF. The implication of this finding is that educators should consider integrating sticking pictures as health promotion media into their teaching methods to enhance students’ knowledge and attitude towards dengue fever prevention.